(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
This work deals with the risk of emergencies and disasters that affect the population in two municipalities in Alto Vale do Itajaí / SC, while discussing the costs of prevention and reconstruction in the management of these risks. Respondents were involved in eminent risk in the municipalities surveyed and also responsible for the security companies that has more than 50 employees. Often the population is exposed to risks, but do not know them. The data reveal that there is still no efficient management of risks in the municipalities surveyed although there is the presence of a hazard. Related information are not consistent and often neglected by public entities. It is concluded that still invests a lot in repairing the damage caused by the disaster rather than prevent them or mitigate them, which surely would have lower investment and programmability.